The Dynamics of the Chinese Business Practice and the Local Elites Behavior: The Legacy of Pseudo-Capitalism in Indonesia’s Local Development (Journal of Governance and Development (JGD), 2023)
The evolution of the Chinese business activities in several Southeast Asian(SEA) countries such as Indonesia, The Philippines, Thailand, and Malaysiais rather difficult to separate from the influence of the state policies and thebehavior of political elites. In Indonesia, the relationship of the Chinesebusinessmen, particularly in big business activities with Suharto regime,known as ‘Orde Baru’ (New Order), shows a model of patron-client behaviorand crony capitalism networks. The accommodation, protection, and accessprovided by the regime has led to the economic capitalization of the Chinesebusiness in Indonesia. In fact, the relationship between Chinese business andNew Order’s regime is mutually beneficial and very tight. After the fall of theNew Order regime in 1998, the political system in Indonesia became moreopen and decentralized (locally known as ‘Otonomi Daerah’ or RegionalAutonomy). This shows the important role of the local government inmaking decision particularly in terms of economy sector and infrastructuredevelopment’s project. The paper aims at three folds: first is to discuss thepattern of the Chinese ethnic business activities in post-New Order regimeand its impact to the local development. Second, to discuss to what extentthe Chinese business practice particularly in real-estate or property sectorinfluenced by the local elites behavior. Third is to discuss whether thepatron-client relationship and crony capitalism behavior in the local contextbetween Chinese businessmen with local elite occurred as in the Suharto’sera or not. The findings show that the pattern of the Chinese business inpost-Suharto’s Indonesia in several business sectors (medium and mediumlargebusinesses) sometimes still rely on the use of networks with local elites.The local government faced a ‘complex dilemma’ in term of developmentprojects, where basically requires substantial capital from big companies, then they often violated the laws to accelerate the development projects. Thepatron-client networks and crony capitalism vaguely occurred among theChinese businessmen and local elite. However, the level of their closeness isnot too visible as in the Suharto’s era. In other circumstances, the Chinesebusinessmen also become superior actors, while the local elites only becomeinferior actor, because the companies actually seemed to be able to controlthe government decision indirectly.